Mechanical properties of cassava starch films as affected by different plasticizers and different relative humidity conditions - Jeannine Bonilla Lagos; Nıvea M. Vicentini; Rodolfo M.C. Dos Santos; Ana Monica Q.B. Bittante; Paulo J.A. Sobral (International Journal of Food Studies)
The influence of plasticizer type (glycerol and sorbitol), its content (starch:plasticizer ratio of 1:0.15; 1:0.20; 1:0.25 and 1:0.30) and the relative humidity conditions (43, 58, 75 and 85%) on the mechanical properties of cassava starch films was studied. Both plasticizers seemed to integrate homogeneously in the film matrix. The incorporation of different concentrations of plasticizers affected the mechanical properties of the cassava starch films. Plasticizer ratio directly influenced the force values of the films, they showed significant flexibility when the plasticizer proportion was increased in the formulation. Under conditions of low relative humidity, sorbitol produced films more resistant to puncture than glycerol. Qualitatively, all the films were less brittle when the plasticizers were incorporated.